Water absorption analysis of oil palm fibre reinforced acrylonitrile butadiene styrene composites by Fick's law - Ahmad, Mohd Nazri; Ishak, Mohamad Ridzwan; Maidin, Nurul Ain; Saharudin, Mohd Shahneel (Penerbit Akademia Baru, 2025)
Over the past twenty years, researchers have become increasingly interested in natural fibres reinforced thermoplastics. The major cause of hydrophilic tendency is the presence of voids and non-crystalline part of these fibres which affects the fibre and polymer matrix adhesion. Therefore, it is important to develop the proper mechanism and understanding the water absorption behaviour of these composites. The aim of this paper is to analyse the water absorption behaviour using Fickian diffusion model. The oil palm fibre reinforced acrylonitrile butadiene styrene (ABS) composites at different fibre loadings (0, 3, 5 and 7 wt %) were fabricated by FDM according to the ASTM D6980 and the water absorption was analysed by a Fickian diffusion model. The results showed that the percentage of water absorption increases with increasing of fibre loadings from 0 wt% to 7 wt%. The result of applying the Fickian model showed that when the fibre loading increased, the D value decreased. On the other hand, when the fibre loading rose, the M∞ value rose as well. The value of the kinetic parameters, n was closer to 0.5. It showed that the absorption process behaved like a Fickian process.